Odpowiedzi

2010-01-24T22:20:01+01:00
Oblicz wartość liczbową wyrażenia dla a= -1 i b=½ .

a (a+2b-3) -b (2a+b-6) + 3 (a-2b)=
a²+2ab-3a-2ab-b²+6b+3a-6b=a²-b²=(-1)²-(1/2)²=
=1-1/4=3/4
1 5 1
2010-01-24T22:23:22+01:00
A+2b-3-2ab+b<kwadrat>-6b+3a-6b=-10b-3-2ab+b<kw>+3a dla a =-1 i b =1/2
-10*-1/2-3-2*-1*1/2+1/2*1/2+3*-1=-5-3+1-3+1/4=-9 i 3/4
2010-01-24T22:24:22+01:00
A (a+2b-3) -b (2a+b-6) + 3 (a-2b)= a² +2ab - 2ab -3a -b² + 6b +3a -6b =a² -b² +3a

• a= -1 i b=½ .

1 - 0,25 = 0,76

Odp: Wartoś wyrażenia wynosi 0,75

;) prosze o naj ;]